Dari Kerajaan Maritim ke Negara Bangsa: Transformasi Politik dan Sosial Asia Tenggara dalam Lintasan Sejarah - Yohanis Kristianus Tampani; Anastasia Funan; Anggi Denada Bees; Esau Lopo; Danial Sain; Florentina Hoar Tetik (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to describe and analyze the transformation process from maritime empires to nation-states in Southeast Asia, as well as the factors that drove it and its impact on regional societies. The study uses a literature study method by collecting and analyzing data from various relevant primary and secondary sources. The results show that Southeast Asia has a long history of maritime empires such as Srivijaya, Majapahit, and Malacca, which became centers of trade, the spread of religion, and the formation of early social structures. The transformation to nation-states was influenced by the influx of European influence, the growth of nationalism, and changes in economic structures. The transformation process included changes in the formation of national borders, government systems, the development of state institutions, as well as changes in social structures, the spread of education, and shifts in cultural values. The impacts of the transformation included increased state sovereignty, economic development, and improvements in the quality of life for the people, but also brought challenges such as ethnic tensions, corruption, and socioeconomic inequality. This study concludes that the transformation process is a complex journey that shapes the characteristics of modern nation-states in Southeast Asia today.